PELATIHAN PEMBUATAN PUPUK ORGANIK DI P4S KELURAHAN KARANGSARI KECAMATAN SUKOREJO KOTA BLITAR - Tri Kurniastuti; Palupi Puspitorini (CV. Ulil Albab Corp, 2023)
The elucidation on making organic fertilizer from starfruit cultivation waste was held to transfer the technology to farmers in utilizing the leftover waste from starfruit cultivation to be healthy, environmentally friendly, and sustainable of starfruit cultivation. Organic fertilizer is essential as a buffer for the soil's physical, chemical, and biological properties to increase fertilizer efficiency and land productivity. The method used in this activity is the elucidation of materials used and the demonstration of organic fertilizer production. The material given was the role and the function of organic fertilizer for soil, environment, and crop yields. Also, the steps of producing organic fertilizer were utilizing the leftover starfruit cultivation and farmer's livestock manure in Karangsari Village. During the training on producing organic fertilizers, the presentation of the material on the benefits of organic fertilizers was going well, and the community's enthusiasm was visible. 28 of 30 invited people attended, meaning the attendance rate was 93%. Many participants actively asked questions, and the discussion went well. During the production of organic fertilizer, participants carried out the activities actively, starting from preparing ingredients and mixing ingredients until the completion of producing organic fertilizer